PP.20.26: INFLUENCE OF CAROTID ARTERY PLAQUE ON ECHOGENICITY OF THE COMMON CAROTID ARTERY INTIMA-MEDIA COMPLEX. (June 2015) - Aizawa, K.; Elyas, S.; Adingupu, D.D.; Casanova, F.; Gooding, K.M.; Mawson, D.; Shore, A.C.; Strain, W.D.; Gates, P.E.
Abstract : Objective: Grey scale median of the common carotid artery intima-media complex (IM-GSM) characterizes the composition of the arterial wall. It is thought to reflect more generalized atherosclerotic vulnerability of the vasculature and may be a biomarker of early atherosclerotic processes in the carotid artery before overt plaque develops. Although a close association between IM-GSM and grey scale median of carotid plaque (PL-GSM) has previously been observed in a population-based study, it is unclear whether IM-GSM differs in individuals with carotid plaque compared to those without. We examined whether IM-GSM was different between individuals with and without the presence of plaque in patients with recently diagnosed cerebrovascular disease (stroke or transient ischaemic attacks) and apparently healthy individuals. Design and method: Ninety-six patients with either stroke or transient ischemic attacks occurring within three months before the study visit (CRVD: 68.6 ± 9.8yrs, 30F) and 82 apparently healthy individuals (CTRL: 63.2 ± 8.7yrs, 42F) were studied. Carotid artery intima-media complex and plaque images were obtained using a Doppler ultrasound machine. IM-GSM and PL-GSM were analysed using semi-automated edge-detection software. Results: Seventy-seven in CRVD (80.2%) and 41 in CTRL (50.0%) had at least one plaque in the carotid arteries. IM-GSM was significantly lower in CRVD than CTRL after adjustment for age and sex (107.1 ± 2.7au vs 122.1 ± 2.9au, p < 0.001). In both groups, IM-GSM was similar between individuals with and without plaque (CRVD: 107.8 ± 2.8au vs 98.0 ± 6.2au, p = 0.17, CTRL: 121.1 ± 4.4au vs 126.1 ± 4.4au, p = 0.43). In univariate analysis, IM-GSM was positively associated with PL-GSM (r = 0.29, p < 0.005) and multivariate regression analysis showed that IM-GSM (β=0.30) was independently associated with PL-GSM along with current smoking (β=-0.22) in the overall data set (total R 2  = 0.14). Conclusions: An early stage of atherosclerotic process (IM-GSM) is associated with an advanced stage of atherosclerotic process (PL-GSM), but the presence of carotid plaque did not significantly influence IM-GSM in either group. We speculate that local factors (e.g. haemodynamic wall shear stress) have an important influence over carotid plaque echogenicity in combination with systemic exposure to risk factors for atherosclerosis.